Faktor-Faktor Yang Berhubungan dengan Kejadian Persalinan Preterm di UPT. Puskesmas Tembuku I - Ni Luh De Dwijasistawati; Ni Wayan Ariyani; Regina Tedja Sulaksana (Midwifery Department of Health Polytechnic, Ministry of Health, Denpasar, 2023)
Preterm birth is still a big problem in Indonesia and has the potential to increase perinatal mortality by 65%-75%, generally associated with low baby weight, namely 2,500 grams and gestational age 37 weeks. At UPT.Puskesmas Tembuku I for the period January 2020 – December 2021, data obtained as many as 542 deliveries, 30 (5.53%) were LBW deliveries and 22 (4.06%) of them were preterm deliveries. This study aims to determine the factors associated with the incidence of preterm delivery at UPT.Puskesmas Tembuku I Year 2020-2021 based on LILA factors, anemia, multiple pregnancies, age, and parity. The research data is secondary data obtained from the cohort of mothers and MCH reports for the period January 2020 to December 2021. This type of research uses a cross sectional analytic method. Sampling using simple random sampling technique with a total sample of 230. The place of research was conducted at UPT.Puskesmas Tembuku I in March-April 2022. The results of this study showed that there was a relationship between LILA factors (p = 0.020), anemia (p = 0.000) , and age (p=0.000) with the incidence of preterm delivery. There was no relationship between the multiple pregnancy factor (p=0.061) and parity factor (p=0.474) with the incidence of preterm delivery. It is recommended that there is an early detection by health workers of factors related to preterm delivery and socialization to pregnant women with KEK (LILA 23.5 cm), anemia and maternal age on the risk of preterm delivery.